Density functional theory study on the coupling and reactions of diferuloylputrescine as a lignin monomer. (May 2022) - Elder, Thomas; del Río, José C.; Ralph, John; Rencoret, Jorge; Kim, Hoon
Abstract: Diferuloylputrescine has been found in a variety of plant species, and recent work has provided evidence of its covalent bonding into lignin. Results from nuclear magnetic resonance spectroscopy revealed the presence of bonding patterns consistent with homo-coupling of diferuloylputrescine and the possibility of cross-coupling with lignin. In the present work, density functional theory calculations have been applied to assess the energetics associated with radical coupling, rearomatization, and dehydrogenation for possible homo-coupled dimers of diferuloylputrescine and cross-coupled dimers of diferuloylputrescine and coniferyl alcohol. The values obtained for these reaction energetics are consistent with those reported for monolignols and other novel lignin monomers. As such, this study shows that there would be no thermodynamic impediment to the incorporation of diferuloylputrescine into the lignin polymer and its addition to the growing list of non-canonical lignin monomers. Graphical abstract: Image 1 Highlights: Diferuloylputrescine has been found in lignin isolated from corn grain fibers. There is evidence that diferuloylputrescine may homo-couple and/or cross-couple with lignin. Density functional theory calculations demonstrate the thermodynamic feasibility of such coupling reactions.